Metagenomics-based analysis of microbial community dynamics and flavor compound correlations during rice-flavor Baijiu brewing - Li, Qun; Zhang, Long; Li, Rui; Tang, Jie; Lin, Bin; Qin, Chunyu; Jiang, Wei; An, Longxu; Zhang, Fan; Shi, Xingxing; Yang, Shengzhi; Yang, Qiang; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
This study aimed to explore the microbial contribution to flavor compound production by analysing the succession patterns and metabolic functional characteristics of microbial communities during Jiuqu preparation, saccharification, and fermentation processes of rice-flavor Baijiu (RFB). The physicochemical parameters during RFB fermentation were systematically monitored, and the volatile flavor profile was characterized using headspace solid-phase microextraction gas chromatography‒mass spectrometry (HS-SPME–GC–MS). Concurrently, metagenomic sequencing was employed to elucidate the microbial community structure and its temporal dynamics throughout the fermentation process. The results of the physicochemical parameters revealed that the reducing sugar content peaked at the end of saccharification and subsequently decreased throughout fermentation, whereas the total acid and total ester contents progressively increased, reaching maximum levels at the fermentation endpoint and maintaining stability. HS-SPME–GC–MS analysis revealed 84 volatile flavor compounds including phenylethanol, ethanol, dimethyl ether, isopentyl alcohol, and acetic acid. Notably, compounds such as L-ethyl lactate, diethyl succinate, and isobutanol were initially synthesized during saccharification and subsequently accumulated during fermentation, emerging as major flavor constituents. Ascomycota and Mucoromycota dominated the fungal community (average relative abundance >1%), whereas Firmicutes and Proteobacteria prevailed among the bacterial phyla. Six genera, Lichtheimia, Kluyveromyces, Lacticaseibacillus, Lactobacillus, Limosilactobacillus, and Schleiferilactobacillus were identified as primary contributors to flavor production during fermentation. Functional analysis revealed that microbial metabolism in fermented mash primarily involved amino acid and carbohydrate metabolism, with glycoside hydrolases (GHs) and glycosyl transferases (GTs) serving as key carbohydrate-active enzymes. This study could improve the comprehensive understanding of the brewing mechanism of RFB and provide a theoretical basis for the development and utilization of microbial resources in the fermented grains and the improvement of RFB quality.